2015
DOI: 10.1523/jneurosci.2731-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Functional Modules for Discrete and Rhythmic Forelimb Movements in the Mouse Motor Cortex

Abstract: Movements of animals are composed of two fundamental dynamics: discrete and rhythmic movements. Although the movements with distinct dynamics are thought to be differently processed in the CNS, it is unclear how they are represented in the cerebral cortex. Here, we investigated the cortical representation of movement dynamics by developing prolonged transcranial optogenetic stimulation (pTOS) using awake, channelrhodopsin-2 transgenic mice. We found two domains that induced discrete forelimb movements in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
76
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(91 citation statements)
references
References 41 publications
15
76
0
Order By: Relevance
“…Although it is not known what exactly the motor map reflects (Histed et al 2009), it has been suggested that motor cortex maps arise from learning-sculpted circuits that support learned movements (Aflalo & Graziano 2006). Indeed, rodent motor cortex appears to be mapped as much by coordinated movements as by somatotopy (Harrison et al 2012, Hira et al 2015, Ramanathan et al 2006), and manipulations of neuromodulators have linked motor maps and motor learning (see the sidebar titled Neuromodulators in the Motor Cortex).
NEUROMODULATORS IN THE MOTOR CORTEX

One interesting line of results that comes from studies of rodent motor maps is related to the role of neuromodulators in learning.

…”
Section: Functional Plasticitymentioning
confidence: 99%
“…Although it is not known what exactly the motor map reflects (Histed et al 2009), it has been suggested that motor cortex maps arise from learning-sculpted circuits that support learned movements (Aflalo & Graziano 2006). Indeed, rodent motor cortex appears to be mapped as much by coordinated movements as by somatotopy (Harrison et al 2012, Hira et al 2015, Ramanathan et al 2006), and manipulations of neuromodulators have linked motor maps and motor learning (see the sidebar titled Neuromodulators in the Motor Cortex).
NEUROMODULATORS IN THE MOTOR CORTEX

One interesting line of results that comes from studies of rodent motor maps is related to the role of neuromodulators in learning.

…”
Section: Functional Plasticitymentioning
confidence: 99%
“…Several research groups began to take advantage of the semi-transparent nature of the mouse skull by generating large, bi-hemispheric windows through either the intact (Guo et al, 2014), or partially thinned skull (Silasi et al, 2013). Although retraction of the skin alone can have some unwanted effects, such as significant brain cooling in anesthetized mice (Kalmbach and Waters, 2012), the reduced invasiveness offered by transcranial windows has made this the preparation of choice in a number of imaging applications (Cang et al, 2005;Yang et al, 2010;Yoder and Kleinfeld, 2002) including wide-field imaging of hemodynamic signals in anesthetized preparations (Kalchenko et al, 2014;White et al, 2011), and targeted photostimulation in awake (Hira et al, 2009) or behaving mice (Hira et al, 2015). So far, however there have been no detailed methodological descriptions for these preparations, nor has this technique been applied for chronic, wide-field functional imaging in awake mice.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, DM and RM are controlled by distinct corticocortical synaptic circuits (Hira et al . 2015) and more indirect corticospinal pathways contribute to RM (locomotion) in rodents (Miri et al . 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The differences in neural mechanisms underlying DM and RM seem to be specifically related to the initiating and the ending of the movements as ongoing RM also differ from the first (Ikegami et al 2010) and the last cycle of RM (van Mourik & Beek, 2004). Moreover, from animal studies it was suggested that different functional anatomical representations in the motor cortex are accompanied by DM and RM dynamics (Hira et al 2015) and that corticospinal pathways engage in DM and RM differently with regards to movement phase (Miri et al 2017). In conclusion, experimental evidence favours the viewpoint that different neural entities control DM and RM.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation